Young star clusters and the structure of the second Galactic quadrant. Issue 2 (18th July 2018) - Molina Lera, J A; Baume, G; Gamen, R
ABSTRACT: Aiming to improve the knowledge of the Galactic structure in the second Galactic quadrant, we selected 10 young open clusters from a sample of more than 200 covered by the SDSS. Our study was based on a photometric data set provided by SDSS and APASS in the visible and by 2MASS and WISE in the infrared. We also carried out spectroscopic observations with GMOS/GEMINI and made use of spectroscopic information available in the literature. The analysis was performed with a suite of tools developed by us to systematically determine the main parameters of the studied clusters, and to identify possible pre-main-sequence populations. We obtained novel parameters and found that the studied clusters are scattered at distances ranging from 1.7 to 8.8 kpc, covering three spiral arms. In particular, we located two of the clusters over the 'Outer Arm' and other two probably belong to the more distant 'New Arm'. Hence, it was possible to get a better picture of the structure of the outer part of the Galaxy. We also obtained traces of coeval star formation processes in all of the selected clusters with a pre-main-sequence population and identified young stellar object candidates in one of them. Regarding the most massive members of the clusters, we discovered 14 B-type stars, eight of them earlier than B3 and another one was identified as a Be star.